Adsorption—Desorption Processes on Mesoscopic Pores Connected to Microscopic Pores of Complex Geometry Using the Ising Model - M.A. Balderas Altamirano; S. Cordero; G. Román; A. Gama Goicochea (Adsorption Science & Technology)
In this work, nitrogen adsorption and desorption onto solid surfaces were studied using computer simulations of the three-dimensional Ising model, for systems with complex porous structures at the mesoscopic and microscopic levels. A hysteresis cycle between the adsorption and desorption processes appears and it was found that its characteristics are dependent on the geometry of the pore and on the strength of the surface–fluid interaction. We also obtained an average adsorption isotherm, which represents a combination of differently shaped pores, and shows robust jumps at certain values of the chemical potential as a consequence of the shape of the pores. A comparison of the results of this study with experimental data is also made. In addition, we report the filling of microscopic pores connected with mesopores. It is argued that these predictions are useful for researchers working on the enhanced recovery of oil and for the design of new nanomaterials, among others.